A Review on the Recent Breakthrough Methods and Influential Parameters in the Biodiesel Synthesis and Purification - S. Silviana; Didi Dwi Anggoro; H. Hadiyanto; Cantika Aulia Salsabila; Kevin Aprilio; Anisa Widia Utami; Febio Dalanta; Afriza Ni'matus Sa'adah (International Journal of Renewable Energy Development, 2022)
Biodiesel has recently received much attention as an energy source with numerous benefits such as high degradability, negligible toxicity, and minimal emissions of carbon monoxide gases as well as particulates. Therefore, this research aims to compare, review, and summarize the conventional and advanced methods of biodiesel production. Currently, some emerging processes that were developed for advanced biodiesel production include microwave-assisted synthesis, ultrasonic-assisted synthesis, supercritical transesterification, and liquid phase plasma discharge technology. The types of feedstocks, catalysts, and operating conditions as the influential parameters in biodiesel synthesis are also discussed. Moreover, in the purification process, the effectiveness of purification depends on the type of catalyst applied in the synthesis process. This research also reviewed and compared several commonly used purification methods such as wet and dry washing, ion exchange and precipitation, complexation, and membrane-based separation that have shown significant results along with the impacts of biodiesel production on environmental and economic sectors